Polygalacturonase and pectin methylesterase activities of CaCl2 treated red-fleshed dragon fruit (Hylocereus polyrhizus) harvested at different maturity - Awang, Yahya; Chuni, Siti Hajar; Tengku Muda Mohamed, Mahmud; Yahya, Hafiza; Mohamad, Rosli (Science Publications, 2013)
Fruits harvested at different maturity possess different biochemical constituents and physiological properties that make the fruits may react somewhat differently to the postharvest treatment. A study to examine the activity of Polygalacturonase (PG) and Pectin Methylesterase (PME) enzymes during storage in dragon fruit (Hylocereus polyrhizus) harvested at 28 days (Index 3) and 34 days (Index 5) after anthesis and postharvest treated with 0, 2.5, 5.0 and 7.5 g L-1 CaCl2 was performed. The PG activity was lower in younger fruit and vice-versa for PME activity. Increasing concentration of CaCl2 effectively reduced the activity of both enzymes. PG activity for fruit treated with 0, 5 and 7.5 g L-1 CaCl2 increased linearly with the time of storage while its activity for the fruit treated with 2.5 g L-1 CaCl2 was lower at the beginning of storage. PG activity of Index 5 fruits increased almost linearly during storage while its activity in Index 3 fruits was low at the early days of storage and later continued to increase until day seven. At both maturity indices, the PME activity was low at the early days of storage and later continued to increase until day seven. Overall, results obtained indicated that CaCl2 postharvest treatment reduced both PME and PG activities thus slowing down the softening process giving an evident that calcium possess a distinguishable role in the reducing softening of fruit, regardless of maturity index.